A necessary condition for EPT graphs and a new family of minimal forbidden subgraphs - Alcón, Liliana Graciela (2010)
An undirected graph G is called an EPT graph if it is the edge intersection graph of a family of paths in a tree. In this paper we define the concept of satellite of a clique and we give a necessary condition to be an EPT graph based on satellites of cliques. We characterize the minimal graphs which do not satisfy the previous condition, as a consequence we present a finite family of minimal forbidden subgraphs for the EPT class.